Late Hip Dysplasia After Normal Ultrasound in Breech Babies: Implications on Surveillance Recommendations. Issue 4 (5th April 2021) - Morris, William Z.; Mayfield, Laura; Beckwith, Terri; Zepeda, Erica; Jo, Chan-Hee; Sucato, Daniel J.
Abstract : Background: There is significant controversy in the literature over rates of late-developing dysplasia following normal screening ultrasound in breech babies, with reported rates varying from 7% to 29%. The purpose of this study is to investigate the rates of radiographic dysplasia in breech babies after a normal ultrasound with a minimum of 1 year of radiographic follow-up. Methods: This study was an institutional review board–approved prospective study of all patients referred by their pediatrician for concern for developmental dysplasia of the hip between July 2008 and August 2014. We identified all subjects with breech presentation and excluded those with an abnormal initial examination/ultrasound or with <12 months of radiographic follow-up. Anterior-posterior pelvis films were obtained after >12 months and acetabular indices (AIs) were measured and compared with contemporary normative data. Dysplasia was diagnosed as >2 SDs above the mean. Results: A total of 654 patients were referred with a history of a breech presentation, and 150 (22.9%) were found to have clinical instability or sonographic evidence of dysplasia on initial presentation and were observed with serial imaging or treated. Of the remaining 504 subjects with a normal clinical examination and screening ultrasound, 133 (26.4%; 74.4% females, 25.6% males) were followed until at least 12 months of age. Of those presenting at age 12 to 14 months, the mean AI was 0.42±0.83 SD above the mean with a skew towards elevated AIs. At the final follow-up (mean: 20.7±6.7 mo), the mean AI was 0.05±0.92 SD above the mean, and only 3/133 (2.2%) patients had a dysplastic hip. No patients underwent treatment other than an observation during the study period. Conclusions: One in 5 breech babies have dysplasia at presentation, but late dysplasia following normal screening ultrasound may be less common than previously reported and may be due to our prolonged follow-up period. We recommend surveillance of breech babies with follow-up visits after 12 months of age since earlier visits may offer limited benefits. Level of Evidence: Level II—prospective prognostic study.